Manuscripts, Politics and Oriental Studies : Life and Collections of Johann Gottfried Wetzstein (1815-1905) in context - Liebrenz, Boris,; Rauch, Christoph, (Islamic Manuscripts and Books, 2019)
Manuscripts, Politics and Oriental Studies commemorates the life and works of Johann Gottfried Wetzstein (1815-1905) as a scholar, manuscript collector, and consul in Berlin and Damascus. Beyond research into Wetzstein's own time, special attention is given to the impact his efforts to acquire manuscripts have had until this day. Several contributions also illustrate contemporary developments that give context to his own career as a scholar and diplomat. The particular focus of this volume allows to explore the history of Oriental scholarship not purely through the lens of academic posts and publications but encourages us to discover lifes such as Wetzstein's, without academic stardom yet laying the material foundations of textual work for generations. Contributors are Kaoukab Chebaro; François Déroche; Faustina Doufikar-Aerts; Alba Fedeli; Ludmila Hanisch †; Michaela Hoffmann-Ruf; Ingeborg Huhn; Robert Irwin; Boris Liebrenz; Astrid Meier; Samar El Mikati El Kaissi; Claudia Ott; Holger Preißler †; Christoph Rauch; Helga Rebhan; Anke Scharrahs; Jan Just Witkam.